Dragonsong - McCaffrey, Anne. (New York : Bantam Books, 1986)
Forbidden by her father to indulge in music in any way, a girl on the planet Pern runs away, taking shelter with the planet's fire lizards who, along with her music, open a new life for her.
Wilson's Children.
Wilson's Junior High School.
Wilson's Senior High School.
7.3
Young Adult
Keywords: Extraterrestrial beings -- Fiction; Music -- Fiction; Pern (Imaginary place) -- Fiction; Science fiction; Extraterrestrial beings -- Fiction; Music -- Fiction; Pern (Imaginary place) -- Fiction; Science fiction